Electrical properties of nanostructured SiN films for MEMS capacitive switches. (28th October 2016) - Koutsoureli, M; Xavier, S; Michalas, L; Lioutas, C; Bansropun, S; Papaioannou, G; Ziaei, A
Abstract: The electrical properties of gold nanorods nanostructured silicon nitride films are comprehensively investigated with the aid of metal–insulator–metal capacitors and RF MEMS capacitive switches. Different nanorod diameters and densities were grown on the bottom electrode and with orientation normal to dielectric film surface. A simple physical model, which does not take the effect of electric field fringing into account, was developed to describe both the DC and low frequency electrical properties. It has been shown that the nanorods distribution and dimensions determine the electrical properties as well as the dielectric charging phenomena of the nanostructured films. Finally, in MEMS switches it has been shown that the nanorods presence does not affect the capacitance variance nor the RF characteristics of the device.